2015
DOI: 10.1093/jjco/hyv107
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of amrubicin at a dose of 45 mg/m2in patients with previously treated small-cell lung cancer

Abstract: Objective: Most of the previous studies of amrubicin in patients with previously treated small-cell lung cancer were conducted at a dose of 40 mg/m 2 . The aim of this study was to assess the efficacy and safety of amrubicin at a dose of 45 mg/m 2 in patients with relapsed or refractory small-cell lung cancer.Methods: Previously treated small-cell lung cancer patients were eligible. Amrubicin at a dose of 45 mg/m 2 was administered on Days 1-3 every 3 weeks. The primary endpoint was the response rate.Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 16 publications
(19 reference statements)
2
10
0
Order By: Relevance
“…Previous studies found that an AMR dose of 40 mg/m 2 showed adequate activity and acceptable toxicity in previously treated SCLC patients . Meanwhile, an AMR dose of 45 mg/m 2 , while effective, produced intolerable toxicities and even treatment‐related deaths in other studies . Sekine et al .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies found that an AMR dose of 40 mg/m 2 showed adequate activity and acceptable toxicity in previously treated SCLC patients . Meanwhile, an AMR dose of 45 mg/m 2 , while effective, produced intolerable toxicities and even treatment‐related deaths in other studies . Sekine et al .…”
Section: Discussionmentioning
confidence: 96%
“…[13][14][15][16]20,21 Meanwhile, an AMR dose of 45 mg/m 2 , while effective, produced intolerable toxicities and even treatment-related deaths in other studies. 22,23 Sekine et al conducted a valuable randomized phase III study that showed that higher incidences of febrile neutropenia and interstitial lung disease of grade 3 or worse occurred with 45 mg/m 2 AMR; they concluded that AMR at 45 mg/m 2 is toxic and intolerable in chemonaïve elderly Japanese patients with ED-SCLC. 24 These findings show that the AMR dose is critical for avoiding fatal adverse events, such as severe neutropenia or febrile neutropenia.…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that amrubicin was efficacious against relapsed ED‐SCLC at 35–40 mg/m 2 . However, administration of amrubicin at 45 mg/m 2 , while effective, produced intolerable toxicities and even treatment‐related deaths in separate studies . Thus, the amrubicin dose is critical to avoid severe or febrile neutropenia.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, although an AMR dose of 45 mg/m 2 was reportedly effective, it produced intolerable toxicities and even treatment-related deaths in other studies. 48,49 Furthermore, a randomized phase III study previously reported by Sekine et al indicated that higher incidences of febrile neutropenia and interstitial lung disease of grade 3 or worse occurred with 45 mg/m 2 AMR; the authors concluded that AMR at 45 mg/m 2 is intolerable in chemo-naïve elderly Japanese patients with ED-SCLC. 27 These findings demonstrate that the appropriate AMR dose is critical for avoiding fatal adverse events, such as severe neutropenia or febrile neutropenia.…”
Section: Toxicity Assessment and Dose Modificationmentioning
confidence: 95%